2021
DOI: 10.1002/ajoc.202100068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3H‐Pyrrolo‐(1,2‐a) Indole‐based Fluorophore Macrocycles and their Stable Cation Radicals

Abstract: Small molecular fluorophores with high quantum yields are of particular interest because of their role in several applications that range from ion sensing to bioimaging. Indole based biomolecules are well known for their fluorescence properties. Pyrrolo[1,2-a]indoles have gained tremendous interest in recent times due to their applicability in various fields such as biomedicine and dye-sensitized solar cells (DSSC). In this article, we report the synthesis of new types of crowned 3H-pyrrolo[1,2-a]indole fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(97 reference statements)
1
11
0
Order By: Relevance
“…The condensation of diol 5 a / 5 b and benzitripyrrane 6 a / 6 b were also carried out by using the other acid catalysts such as TFA and PTSA under different reaction conditions, but the best yields of crowned macrocycles 1 – 3 were obtained only with 0.1 equivalent of BF 3 .OEt 2 as an acid catalyst. The macrocycles 1 – 3 are highly soluble in common organic solvents like CH 2 Cl 2 , CHCl 3 , THF, and HR‐MS analysis showed four mass units less than the expected macrocycle 4 indicating the occurrence of two intramolecular fusion reactions between pyrrolic “N” and benzene “C” to create two pyrrolo[1,2‐a]indole units as a part of the macrocyclic skeleton to form macrocycles 1 – 3 as we noted previously with macrocycle IV [20] . The formation of macrocycles 1 – 3 with two pyrrolo[1,2‐a]indole moieties was later confirmed by obtaining crystal structure of macrocycle 2 (vide‐infra).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The condensation of diol 5 a / 5 b and benzitripyrrane 6 a / 6 b were also carried out by using the other acid catalysts such as TFA and PTSA under different reaction conditions, but the best yields of crowned macrocycles 1 – 3 were obtained only with 0.1 equivalent of BF 3 .OEt 2 as an acid catalyst. The macrocycles 1 – 3 are highly soluble in common organic solvents like CH 2 Cl 2 , CHCl 3 , THF, and HR‐MS analysis showed four mass units less than the expected macrocycle 4 indicating the occurrence of two intramolecular fusion reactions between pyrrolic “N” and benzene “C” to create two pyrrolo[1,2‐a]indole units as a part of the macrocyclic skeleton to form macrocycles 1 – 3 as we noted previously with macrocycle IV [20] . The formation of macrocycles 1 – 3 with two pyrrolo[1,2‐a]indole moieties was later confirmed by obtaining crystal structure of macrocycle 2 (vide‐infra).…”
Section: Resultssupporting
confidence: 61%
“…Since the macrocycles 1 – 3 are highly electron rich and our earlier study on similar kind of macrocycle IV , which is contracted compared to the compounds 1 – 3 showed that these types of compounds can easily form cation radicals, so we have oxidized these macrocycles 1 – 3 by treating them with TFA as well as AgSbF 6 and CuCl 2 [20] . The macrocycles 1 – 3 upon treatment with TFA readily formed cation radicals 1 – 3 .+ as evident from clear colour change from violet to blue and confirmed by electron paramagnetic resonance and spectral absorption studies [27] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crowned fused expanded porphyrins 4 – 6 were synthesized over sequence of steps as shown in Scheme 1. The diol 8 was prepared by subjecting di‐aldehyde compound 7 for Grignard reaction conditions with different aryl bromides whereas the di‐aldehyde compound 7 was prepared by treating 4‐hydroxybenzaldehyde with 1,4‐ bis (chloroethyl) ether in DMF at reflux as reported previously [34] . On the other hand, 2,6‐dithienylpyridine 9 was treated n‐BuLi in THF followed by p ‐tert‐butylbenzaldehyde to afford pyridine based diol 10 which was then treated with excess pyrrole in the presence of catalytic amount of BF 3 ⋅ OEt 2 in CH 2 Cl 2 followed by simple column chromatographic purification afforded pyridine based pentapyrrane 11 [26] .…”
Section: Resultsmentioning
confidence: 99%
“…During our course of investigations on the synthesis of crowned macrocycles, we realized that pyrrolo [1,2-a]indole group as a part of macrocycle can be created by the intramolecular fusion reaction. [19] In pyrrole containing macrocycles, there is a very high tendency for the pyrrole to undergo intramolecular fusion with adjacent phenylene ring carbon to generate pyrrolo [1,2-a]indole as a part of the macrocyclic framework. E.g.…”
Section: Introductionmentioning
confidence: 99%